(untitled) (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2016)
The results of extensive studies that analyzed the existence and meaning of correlations between the economic growth and the financial market development lead us to a more thorough study of these correlations. Therefore, we performed a broad study of the developing countries from around the world (the developing part of each region constructed by the World Bank through its Statistics Bureau). The regions taken into analysis were: Europe and Central Asia, South Asia, East Asia and the Pacific, the Arab world, Latin America & and the Caribbean, the Middle East and North Africa, and Sub-Saharan Africa. For comparison purposes, we have also included in the sample the North American countries, the Euro Area and the European Union as a whole, because these last three areas are the main benchmarks of the financial markets. The results are consistent with those from previous studies on the subject and vary depending on region and financial indicator considered.